Inspektorat Grodno Armii Krajowej .......... 509 - Kordas, Karol (Kresowi żołnierze Armii Krajowej: Historia – Polityka – Pamięć, 2024)
HOME ARMY INSPECTORATE GRODNOGrodno was already an important military point on the map of the Second Polish Republic before the Second World War, as the Corps District Command number III was stationed there. In September 1939, this city particularly suffered at the time of the Soviet Union’s aggression against Poland. The last days of its freedom have gone down in historiography as the The Defence of Grodno 1939. As the Soviet occupation began, the nucleus of a civilian and military conspiracy began to emerge in the city and surrounding villages. However, it was during the German occupation that the development of independence groups in the Grodno area gained momentum. The article focuses mainly on the organisations that, as part of the unification action launched in 1942, became part of the Home Army, or even earlier were incorporated into the Union of Armed Struggle. Thus, the text describes the activities of the Polish underground from 1939-1945, its development, structure, as well as its participation in the Operation Tempest on the territory of the Inspectorate AK Grodno. The article concludes with an epilogue presenting the fate of the soldiers who resisted and undertook another fight against the Soviet Union.